“The Jews” in the Fourth Gospel: Another Perspective - Moloney, Francis J. (Pacifica, 2002)
The discussion of the use of the expression “the Jews” in the Fourth Gospel continues to draw the attention of many scholars. Publications abound, and this scholarly activity is justified, given the overall hostility of the Johannine Jesus to “the Jews”. Most scholarship, understandably, starts from the 71 uses of the expression in the Gospel, and attempts to formulate some historical, literary or theological explanation for the hostility between the Johannine Jesus, Johannine Christians, and “the Jews”. The present study focuses initially on other related, but less used, expressions: “Israel”, “the nation”, and “the people”. Only after this analysis are some questions asked of the use of “the Jews” in the Fourth Gospel, suggesting that the fundamental argument of the Fourth Gospel is that people from all ethnic backgrounds, Jew and Gentile, have been called to form “Israel”, the people of God.